ФИТОРЕМЕДИАЦИОННЫЙ ПОТЕНЦИАЛ ДИКОРАСТУЩИХ ВИДОВ РАСТЕНИЙ (Experimental biology, 2017)
Presented results about possible practical use of wild plants for phytotechnology of pesticide-contaminated soil.
Keywords: phytotechnology; pesticide-contaminated soil